2022
DOI: 10.1093/oncolo/oyac163
|View full text |Cite
|
Sign up to set email alerts
|

FDA Approval Summary: Brexucabtagene Autoleucel for Treatment of Adults With Relapsed or Refractory B-Cell Precursor Acute Lymphoblastic Leukemia

Abstract: In October 2021, the FDA approved brexucabtagene autoleucel (brexu-cel), a CD19-directed chimeric antigen receptor (CAR) T-cell therapy, for the treatment of adult patients with relapsed or refractory B-cell precursor acute lymphoblastic leukemia (B-ALL). Approval was based on the phase II portion of ZUMA-3, a single-arm, open-label, multicenter trial that evaluated a single infusion of brexu-cel, preceded by lymphodepleting chemotherapy with cyclophosphamide and fludarabine, in this population. Efficacy was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…KTE-X19 is another CAR-T cell product which is approved in the USA (as brexucabtagene autoleucel) and in the European Union (EU) (as autologous anti-CD19-transduced CD3+ cells) in 2021 for relapsed or refractory B-ALL. 15,18 Currently, it is an approved CAR-T cell therapy for relapsed or refractory B-ALL in adults 18 years and older and the only approved CAR-T cell product in patients over age 25. The CAR protein of brexucabtagene autoleucel has a murine scFv specific to human CD19 linked to two signaling domains derived from human CD28 and CD3ζ.…”
Section: Brexucabtagene Autoleucelmentioning
confidence: 99%
See 3 more Smart Citations
“…KTE-X19 is another CAR-T cell product which is approved in the USA (as brexucabtagene autoleucel) and in the European Union (EU) (as autologous anti-CD19-transduced CD3+ cells) in 2021 for relapsed or refractory B-ALL. 15,18 Currently, it is an approved CAR-T cell therapy for relapsed or refractory B-ALL in adults 18 years and older and the only approved CAR-T cell product in patients over age 25. The CAR protein of brexucabtagene autoleucel has a murine scFv specific to human CD19 linked to two signaling domains derived from human CD28 and CD3ζ.…”
Section: Brexucabtagene Autoleucelmentioning
confidence: 99%
“…In the ZUMA‐3 trial, BCA was found to be more profound in patients with CR/CRi than in patients without CR/CRi. In a study evaluating a CD19‐directed CAR‐T cell therapy (PLAT‐02) in relapsed/refractory B‐ALL, 13 at a median follow‐up duration of 9.6 months, 2–27 the median expected duration of BCA was 3 months (95% CI, 2.07–6.44). Eighteen of the 40 patients relapsed after achieving MRD‐negative CR.…”
Section: Factors That May Impact the Success Of Cd19‐directed Car‐t C...mentioning
confidence: 99%
See 2 more Smart Citations
“…Acute lymphoblastic leukemia (ALL) is a rare form of leukemia in adults� 1 It accounts for approximately 5% of all adult leukemia cases in Canada� Among these ALL cases, 80% are of B-cell lineage and the B-cell precursor ALL is found in 75% of adult ALL� About 50% of the patients who have B-cell precursor ALL have relapsed or refractory (R/R) disease� The estimated prevalence and incidence of R/R B-cell precursor ALL is 1,148 and 58 people, respectively, based on an estimated population in 2021 in Canada� 2 Typical clinical presentations of ALL are associated with anemia, neutropenia, and/or thrombocytopenia due to bone marrow involvement� Although more than 80% of adult patients with newly diagnosed ALL will achieve a complete remission (CR) with intensive induction chemotherapy, the majority of these patients will ultimately relapse and the prognosis is poor� 3 For patients with R/R B-cell precursor ALL, treatment options include cytotoxic chemotherapy regimens, targeted therapies, allogeneic stem cell transplant (allo-SCT) and the emerging chimeric antigen receptor T (CAR T)-cell therapy� 4,5 CAR T-cell therapy is a treatment in which T lymphocytes are removed from a patient via apheresis, transduced ex vivo with a gene rendering them immunogenic against certain cancer cells, grown, and subsequently reinfused in to the patient� The activated T-cells then circulate, attack, and kill the targeted cancer cells� 5 After the induction therapy, the patients should proceed to allo-SCT as soon as possible if they are eligible, to consolidate the treatment effect obtained from the initial induction therapy� 6 Brexucabtagene autoleucel (brexu-cel; brand name Tecartus) is a CD19-directed genetically modified autologous T-cell immunotherapy that binds to CD19-expressing cancer cells and normal B-cells� 7 On November 16, 2022, brexu-cel was approved by Health Canada for the treatment of adult patients with R/R B-cell precursor ALL� 7 The sponsor's reimbursement request is the same as the Health Canada indication� Brexu-cel is a single-dose, one-time treatment in a patient-specific infusion bag. Each patient-specific, singleinfusion bag of brexu-cel contains a suspension of anti-CD19 CAR-positive viable T-cells in approximately 68 mL for a target dose of 1 × 10 6 CAR-positive viable T-cells per kg of body weight, with a maximum of 1 × 10 8 CAR-positive viable T-cells for patients weighing 100 kg or more� 7…”
Section: Introductionmentioning
confidence: 99%